Immersive Spatial Computing: How Technology Can Improve Science Content Reading and Vocabulary in Elementary Schools - Leonard Annetta; Ashley Johnson; Mark H. Newton; Yvonne Franco (Education Sciences)
Elementary school curricular standards in the United States emphasize mathematics and literacy, while social studies and science are often left behind. Integrating science instruction with either mathematics or literacy is a strategy some teachers use to teach skills and concepts in both disciplines. Understanding science at a young age is reliant on grasping vocabulary that is new to the learner. Integrating visual imagery into reading instruction improves students’ comprehension, enhances retrieval, and increases retention. The media-based reading enhancement of text through spatial computing has begun to show promise for the integration of science vocabulary and reading comprehension, especially for low-proficiency readers. This paper provides a literary rationale for technology-enhanced intervention, provides examples of a study conducted to test the efficacy of such an intervention, presents the implications of the study’s findings, and discusses future avenues for how spatial computing might be used in science and literacy instruction in the future.